Pelaksanaan Tradisi Budaya Karapan Kerbau Masyarakat Sumbawa dalam Mempertahankan Nilai Kearifan Lokal - Astuti, Eni Ayu; Banowati, Eva; Tjahjono, Heri; Santoso, Apik Budi; Suharini, Erni (Ideas Publishing, 2024)
Buffalo racing is a tradition, custom and game of the people of Sumbawa which is still held and has become a community habit. The aim of the research is to find out the implementation of the buffalo racing culture and the values contained therein which maintain existing local wisdom. The method used in this research is descriptive qualitative obtained from sources. Meanwhile, data collection techniques use observation and interview techniques. The results of research into the implementation process of the karapan buffalo tradition started from forming a committee, providing a location, preparing a pair of buffalo, a list of participants, Sandro going around the saka, the buffalo being dressed in noga and coral, the running of the buffalo bepan tradition, and distribution of prizes. Meanwhile, the values contained in the buffalo karapan tradition are mutual cooperation, culture and economics.